2019
DOI: 10.1097/mlr.0000000000001120
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid Expansion at Title X Clinics

Abstract: Background.-Title X supports access to family planning and preventive care services. Given its focus on low-income clients, Title X clinics may have been particularly affected by the Affordable Care Act's Medicaid expansion. Objectives.-To examine the impact of the Affordable Care Act's Medicaid expansion on Title X client volumes, health insurance coverage, and contraceptive method mix. Research Design.-A difference-indifferences design compared changes in the outcomes of interest before and after expansion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…11 Recent studies suggest that the number of women receiving contraceptive services in primary care settings increased in Medicaid expansion states after ACA implementation, [12][13][14] and more women in safety net clinics used insurance to pay for contraceptive services after Medicaid expansion. 15 Research to date on publicly funded contraceptive services has focused on 1 of 3 mechanisms (Medicaid, single payers [eg, state family-planning programs], 16 or federal programs [Title X] [17][18][19] ) or has included only clinics with a reproductive health focus or those known to provide publicly funded contraceptive services. [20][21][22] We have little evidence collected across the safety net system that also includes programs, such as Title X, that pay for contraceptive services in the safety net.…”
Section: Introductionmentioning
confidence: 99%
“…11 Recent studies suggest that the number of women receiving contraceptive services in primary care settings increased in Medicaid expansion states after ACA implementation, [12][13][14] and more women in safety net clinics used insurance to pay for contraceptive services after Medicaid expansion. 15 Research to date on publicly funded contraceptive services has focused on 1 of 3 mechanisms (Medicaid, single payers [eg, state family-planning programs], 16 or federal programs [Title X] [17][18][19] ) or has included only clinics with a reproductive health focus or those known to provide publicly funded contraceptive services. [20][21][22] We have little evidence collected across the safety net system that also includes programs, such as Title X, that pay for contraceptive services in the safety net.…”
Section: Introductionmentioning
confidence: 99%
“…14,30,31 During our 2012-2018 study period, Delaware saw a significant increase in use of long-acting reversible contraceptives in Title X and Medicaid populations. 32,33 A statewide data brief indicated that there was 107% increase in reversible contraceptive methods during 2012-2018, and a 17% percent increase in the percent of Delaware women indicating their pregnancy was intended. 34 Although our study did not find statistically significant differences in effective postpartum contraceptive use among women with an NAS-affected and non-NAS delivery, the low prevalence of effective postpartum contraceptive methods for both groups suggest that sustained and continued statewide efforts that are non-coercive and culturally appropriate may be needed to increase access to effective methods of contraceptives.…”
Section: Discussionmentioning
confidence: 99%
“…The affordability scales had the highest access scores, which affirmed existing clinic policies ensuring the affordability of services. FQHC clinics scored higher on the affordability: insurance policy subscale than HD clinics, suggesting that Title X clinics are not constrained by the insurance contracts accepted at the clinic ( Boudreaux et al, 2019 ). Many patients who seek care at Title X clinics are uninsured, and of patients who have health insurance, most do not use health insurance for the visit because insurance may not cover specific services or due to confidentiality concerns ( Kavanaugh et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%